Al-Jāḥiẓ : in praise of books - Montgomery, James, 1771-1854. (Edinburgh Studies in classical arabic literature)
Al-Jahiz was a bibliomaniac, theologian, and spokesman for the political and cultural elite, a writer who lived, counselled and wrote in Iraq during the first century of the 'Abbasid caliphate. 'In Praise of Books' explores the centrality of books to Al-Jahiz's work and to the society he lived in.